2023
DOI: 10.1200/jco.22.01440
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Adjuvant Chemotherapy for Breast Cancer in Older Women: Results From the Prospective Multicenter HOPE Trial

Abstract: PURPOSE Older women with high-risk early breast cancer (EBC) benefit from adjuvant chemotherapy, but their treatment is frequently complicated by toxic side effects, resulting in dose reductions and delays. This makes it challenging for oncologists to maintain a relative dose intensity (RDI) ≥ 85%, as recommended for optimal curative-intent treatment. Understanding which women are at risk of receiving suboptimal RDI may inform treatment discussions and guide early, targeted supportive care or geriatric comanag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
(89 reference statements)
2
12
0
Order By: Relevance
“…Although trials conducted over 10 years ago had lower RDIs, including one of women randomly assigned to supervised resistance exercise versus Aerobic exercise versus UC, which found RDIs of 90%, 87%, and 84% in the three groups, respectively, our chemotherapy completion rates are similar to more recent trials. 31 Sedrak et al 31 found 80% of older patients with breast cancer received at least 85% RDI. In recent years, shorter course chemotherapy regimens have been prescribed resulting in higher RDIs.…”
Section: Discussionmentioning
confidence: 99%
“…Although trials conducted over 10 years ago had lower RDIs, including one of women randomly assigned to supervised resistance exercise versus Aerobic exercise versus UC, which found RDIs of 90%, 87%, and 84% in the three groups, respectively, our chemotherapy completion rates are similar to more recent trials. 31 Sedrak et al 31 found 80% of older patients with breast cancer received at least 85% RDI. In recent years, shorter course chemotherapy regimens have been prescribed resulting in higher RDIs.…”
Section: Discussionmentioning
confidence: 99%
“…12 More recently, the correlation of the RDI with the survival outcomes has been reported specifically for older women with early ER-positive and HER2-negative BC, treated with various adjuvant chemotherapy regimens in the “Hurria Older PatiEnts with BC (HOPE) Study” (ClinicalTrials.gov identifier: NCT01472094). 13 HOPE is a prospective, multicenter study of patients older than 65 years with early BC, treated with standard chemotherapy, designed to comprehensively capture multidimensional geriatric, clinical, and treatment-related data. In a secondary, preplanned analysis of HOPE, the 5-year OS rate was 80% and 91% with RDI below and above 85%, respectively (multivariate hazard ratio [HR], 2.47; 95% CI, 1.20 to 5.10; P = .01).…”
Section: Clinical Challenges In Treatment and Relevant Literaturementioning
confidence: 99%
“…14,15 For older women and men with BC, we prefer evidence-based treatments that have demonstrated to improve survival. On the basis of the prespecified secondary analysis of the HOPE trial, 13 TC is a preferred regimen, with primary granulocyte colony stimulating factors prophylaxis, because TC has been independently associated with RDI > 85% and better survival outcomes, as opposed to AC- and CMF-like regimens.…”
Section: Our Approach To Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Age has also been associated with survival in patients with BC. Both younger and older age have been associated with differences in treatments and adherence as well as worse mortality . Body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) has also been shown to be associated with BC survival, although the role of BMI in racial and ethnic survival disparities, particularly among groups that are underreported and underrepresented in clinical trials, such as Hispanic patients, merits additional study .…”
Section: Introductionmentioning
confidence: 99%